Pengelolaan Barang Bukti Penyitaan Dan Pertanggung Jawabannya(RUPBASAN SURAKARTA) - Setiawan, Arif; , Hartanto, S.H., M.Hum; , Kuswardani, S.H., M.Hum (2016)
RUPBASAN is the home state storage of seized objects that are based on the provisions in the Criminal Code article KUHAP 44 which explained that the confiscated objects stored in the object storage house confiscated countries. in Surakarta itself there Rubasan first class that was established in 2003 and has the tasks of the state and the storage of seized objects swag country in the city of Surakarta , Sukoharjo district , District Karangannyar . Rupbasan Surakarta in carrying out its duties regarding the receipt , investigation and assessment , registration , storage , maintenance , mutating , security and reporting of objects are stored in the Rupbasan set in the Decree of the Director General of Corrections No. : E1.35 . PK.03.10 of 2002 on implementation guidelines and technical instructions and state management of objects confiscated booty RUPBASAN units throughout the country .